2020
DOI: 10.1155/2020/6937154
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory Markers in the Serum of Prepubertal Children with Down Syndrome

Abstract: Down Syndrome (DS) is the most common chromosomal disorder. Although DS individuals are mostly perceived as characterized by some distinct physical features, cognitive disabilities, and cardiac defects, they also show important dysregulations of immune functions. While critical information is available for adults with DS, little literature is available on the neuroinflammation in prepubertal DS children. We aimed to evaluate in prepubertal DS children the serum levels of nerve growth factor (NGF) and brain-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…In our research, the concentration of amniotic fluid A1AT was significantly lower in the study group compared to the control group. The results suggest that a decrease in the A1AT concentration combined with aggravated inflammation processes and oxidative stress observed in T21 pregnancy may negatively impact plural comorbidities and the occurrence of fetal malformations [48][49][50]. A1AT deficiency combined with the decreased vitamin D levels observed in our study could have a multitude of effects of deregulated paths in T21 pregnancy development [44].…”
Section: Main Findingsmentioning
confidence: 58%
“…In our research, the concentration of amniotic fluid A1AT was significantly lower in the study group compared to the control group. The results suggest that a decrease in the A1AT concentration combined with aggravated inflammation processes and oxidative stress observed in T21 pregnancy may negatively impact plural comorbidities and the occurrence of fetal malformations [48][49][50]. A1AT deficiency combined with the decreased vitamin D levels observed in our study could have a multitude of effects of deregulated paths in T21 pregnancy development [44].…”
Section: Main Findingsmentioning
confidence: 58%
“…Although neurodiagnostic anomalies were observed, no speci c pattern emerged as predictive of the disease or response; yielding the need to interpret all studies as biomarkers of cerebral dysfunction as opposed to being diagnostic or con rmatory of DSRD. Although serum data was of limited value due to low n in this study, it is noteworthy that that elevations in IL-10 were observed as chromosome 21 encodes for the beta subunit of this interleukin and may provide a fast-forward mechanism of disease in DSRD given that levels of this interleukin have previously been identi ed as no different than neurotypical individuals 17 .…”
Section: Discussionmentioning
confidence: 82%
“…Despite DS being the most common chromosomal aberration occurring in all races, the pathological process, as well as the incorrect division of DNA material, are not yet fully understood [ 21 , 22 , 23 ]. It has been demonstrated that pregnant women with a DS fetus suffer from lipid disorders related to disturbed cholesterol metabolism and lipid transport; incorrect distribution of VLDL, LDL, and lipid peroxidation [ 4 ]; and altered concentration of sphingolipids, which leads to improper myelination of fetal neurons [ 24 ].…”
Section: Discussionmentioning
confidence: 99%